Cytoskeleton Structure, Dynamics, Function and Disease - Jimenez-Lopez, Jose C. (IntechOpen, 2017)
The cytoskeleton is a highly dynamic intracellular platform constituted by a three-dimensional network of proteins responsible for key cellular roles as structure and shape, cell growth and development, and offering to the cell with "motility" that being the ability of the entire cell to move and for material to be moved within the cell in a regulated fashion (vesicle trafficking). The present edition of Cytoskeleton provides new insights into the structure-functional features, dynamics, and cytoskeleton's relationship to diseases. The authors' contribution in this book will be of substantial importance to a wide audience such as clinicians, researches, educators, and students interested in getting updated knowledge about molecular basis of cytoskeleton, such as regulation of cell vital processes by actin-binding proteins as cell morphogenesis, motility, their implications in cell signaling, as well as strategies for clinical trial and alternative therapies based in multitargeting molecules to tackle diseases, that is, cancer.